Google Apps, Pembelajaran, onlin Pemanfaatan Google Apps Untuk Meningkatkan Keahlian IT Pada Guru SMPS Bina Satria - Aliyah, Siti; Desi, Efani; Elhias Nst, Mas Ayoe; Tahel, Fithry; Darma, Surya (LPPM Universitas Potensi Utama, 2024)
The learning and evaluation process that has been carried out using information technology in the online learning process has now been implemented in all schools in Indonesia. Since the Covid-19 pandemic occurred, the school has instructed teachers to teach online to students at SMPS Bina Satria. However, with the switch to an online-based learning system, it has created problems for teachers and school administration, the problems that exist are the lack of information technology facilities in the form of computers/laptops and internet networks provided to SMPS Bina Satria, and also reduced knowledge among teachers - teachers in creating online-based learning media which makes the teaching and learning process run less well. To overcome the existing problems, researchers and the team agreed to find a solution by holding training on the use of Google Apps to improve IT skills for SMPS Bina Satria teachers as a medium for document storage, administrative processes and learning evaluation media. The method used by researchers and the team in implementing this training was directly with teachers and school administration. The result of this training is that teachers and school administration have the expertise to use Google Apps independently according to their needs